Psychological impact of COVID19 on community pharmacists and pharmacy technicians - Carmen Baldonedo-Mosteiro; Sara Franco-Correia; Maria-Pilar Mo (Elsevier, 2022)
Background: The unique situation related to the COVID-19 outbreak and the consequent worldwide lockdown can have a psychological impact on specific populations. Community pharmacists and pharmacy technicians, as essential healthcare workers on the front line who continue to do their jobs during this pandemic, can also experience psychological distress. Few data are available on the mental health impact of the COVID-19 pandemics on this population. Objectives: This study aimed to assess the psychological impact of COVID-19 on Spanish community pharmacists and pharmacy technicians during lockdown, and to identify factors contributing to psychological distress. Methods: A cross-sectional, quantitative, correlational study was designed including 1162 pharmacy team members. The Impact of Event Scale revised was used to assess the psychological impact. Data collection was performed by emailing the instrument to individuals or by using social networks. Results: Overall participants, almost 70% revealed severe levels of psychological impact. The outbreak of COVID-19 has significantly affected community pharmacy workers, the degree of which is related to gender, age, and feelings of fear/stress. Conclusions: In the initial phase of the lockdown associated with the COVID-19 outbreak, the majority of the respondents rated the psychological impact as severe. Our findings allow for the identification of factors associated with a greater psychological impact.